2021
DOI: 10.3390/w13121669
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration Measurement and Estimation of Crop Coefficient for Native Plant Species of Green Roof in the Tropics

Abstract: Extensive green roof is one of the sustainable urban stormwater management alternatives to manage and mitigate the urban surface runoff. In order to implement green roofs more effectively, suitable plant species and substrate components for tropical climate must be identified. The aim of this study is to investigate the evapotranspiration (ET) behaviors in extensive green roofs based on different substrate types and local native plant species. Four green roof test beds containing pro-mixing pot and burn soils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Few criteria such as resistance to extreme weather condition, low growing plant and compact plant canopy must be taken into consideration in selecting plant species for extensive green roof. Based on these findings from previous studies, sedum plant was proved as the most suitable type of plant species to be implemented in extensive green roof due to its high resistance to extreme weather and low growing characteristics as it doesn't grow above the implemented PV panel [18,27]. Another important characteristic of sedum plant species is high solar radiation tolerance.…”
Section: Study Areamentioning
confidence: 90%
See 2 more Smart Citations
“…Few criteria such as resistance to extreme weather condition, low growing plant and compact plant canopy must be taken into consideration in selecting plant species for extensive green roof. Based on these findings from previous studies, sedum plant was proved as the most suitable type of plant species to be implemented in extensive green roof due to its high resistance to extreme weather and low growing characteristics as it doesn't grow above the implemented PV panel [18,27]. Another important characteristic of sedum plant species is high solar radiation tolerance.…”
Section: Study Areamentioning
confidence: 90%
“…These sedum plants can be easily obtained from the local nursery in the form of cuttings. Earlier study conducted on the suitability of plant species for green roof in Malaysia has confirmed that sedum performed better than grass plant species in term of survival rate and rainwater retention capacity [27]. Portulaca Grandiflora is able to survive in the harsh environment conditions and has the ability of rapid multiplication, less maintenance, have short and soft roots, and provides good ground coverage.…”
Section: Study Areamentioning
confidence: 98%
See 1 more Smart Citation
“…The analyzed green roof sample has a dimension of 80x60 (l × w) cm with the perimeter of the box made by a thin steel grid to maximize the green surface; the monitoring sensors have been positioned in the middle of the sample to minimize the boundary effect. According to the existing literature [33], the sample set-up is suitable for the thermo-hygrometic green roof analysis. Fig.…”
Section: Experimental Set-up and Sensor Implementationmentioning
confidence: 99%
“…Generally, extensive green roofs are equipped with self-sustaining plant species which require low irrigation and can survive water runoff more effectively [30] thus, they appear beneficial in dry and hot seasons [31]. They supply building energy savings mainly through the substrate evapotranspiration process, essential for releasing cooling effects [32][33][34] and reducing the cooling load of buildings [34,35], the VOC mixture and contributing to the CO 2 sequestration [36]. Contrariwise, intensive green roofs show low performance in saving cooling energy due to the limited biodiversity.…”
Section: Introductionmentioning
confidence: 99%